Unveiling the Impact of the COVID-19 Pandemic (2019-2021) on Inequality, Poverty, and Food Security in Indonesia - Iannone, Aniello (Politika: Jurnal Ilmu Politik, 2023)
This study analyzes the consequences of the COVID-19 pandemic on increasing poverty, food insecurity, and malnutrition in Indonesia. Specifically, the paper focuses on the effects of COVID-19 from 2019 to 2021 on poverty levels and access to food. The pandemic has emerged as a potential cause of food insecurity in the country, primarily due to the decline in purchasing power among individuals facing unemployment or income losses, particularly affecting the middle and poor classes. In response to these impacts, the Indonesian government has implemented various policies, although their success in addressing the issues has been varied. This paper is based on desk-based research, utilizing existing published literature on the topic. The literature has been thoroughly reviewed and analyzed to provide insights into the observed points that require attention. The primary factor driving the rise in food insecurity is the increased costs of basic food items resulting from the pandemic. Drawing from the social inequality Marxist theory and the theory of capabilities proposed by Amartya Sen, this paper examines how the COVID-19 pandemic has contributed to increased injustice, poverty, and inequality. Furthermore, it explores how these issues have been exacerbated by deeper-rooted factors associated with legal and economic policies in Indonesia.